Invention in energy technologies: Comparing energy efficiency and renewable energy inventions at the firm level - Sascha Rexhäuser; Andreas Löschel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Many countries, especially in Europe, have ambitious goals to transform their national energy systems towards renewable energies. Technological change in both renewable production and efficient use of energy can help to make these targets come true. Using a panel of German firms linked to the PATSTAT patent data, we study invention in both types of energy technologies and how their inventors differ in terms of central firm-specific characteristics. More importantly, we study the relation between conventional (i.e. non-energy) invention and energy invention within the firms. The results from dynamic count data models point to a stimulating effect of conventional inventions for energy efficiency technologies but have no effect on inventions in renewable energies.
urn:nbn:de:bsz:180-madoc-368698
Keywords: 330; innovation; invention; renewable energy; energy efficiency; dynamic count data